NMR-Derived Salt Bridges in Insulin Analogue: Resolving Artifactual Overbinding in Molecular Dynamics via Charge Scaling - Le Nguyen, Ngoc Lan; Žák, Jiří; Jungwirth, Pavel; Lepšík, Martin (The journal of physical chemistry letters, 2025)
Salt bridges are ionic interactions that are of great importance in protein recognition. However, their structural description using X-ray crystallography or NMR may be inconclusive. Classical molecular dynamics (MD) used for the interpretation neglects electronic polarization, which results in artifactual overbinding. Here, we resolve the problem via charge scaling, which accounts for electronic polarization in a mean-field way. We study three salt bridges in insulin analogue. New NMR ensembles are generated via NOE-restrained MD using ff19SB and CHARMM36m force fields and the scaled-charge prosECCo75. Tens of μs of unrestrained MD show in a statistically converged manner that ff19SB induces a non-native salt bridge. This behavior is quantified via umbrella sampling of salt bridge dissociation, which indicates a rather high strength of up to 4 and 5 kcal mol-1 for CHARMM36m and ff19SB, respectively. In contrast, prosECCo75 gives a biologically reasonable dissociation barrier of 1 kcal mol-1. Our results indicate that a physically justified description of charge-charge interactions within a nonpolarizable MD framework reliably describes aqueous biomolecular systems.